Ventricular fibrillation by anaphylaxis following consumption of blue‐skinned fish. Issue 2 (12th August 2015) - Otsubo, Saori; Nishiyama, Takashi; Okada, Naoki; Ando, Yukihiro; Yamada, Katsumi; Maeda, Yuji; Nishimura, Yusuke
Abstract : Case: Approximately 4 h after eating mackerel sushi, a 65‐year‐old man developed generalized itchiness and redness, after which he became unresponsive. He went into a state of ventricular fibrillation but after he was defibrillated twice, his heartbeat returned. The electrocardiogram obtained immediately after hospitalization showed some ST‐segment depression, but a subsequent electrocardiogram showed improvement. Coronary CT showed no obvious stenosis or plaque in the coronary artery. Outcome: Results of an IgE‐RAST test confirmed that the level of allergen‐specific IgE for mackerel measured <0.10 UA/mL, while the level for anisakis was 1.91 UA/mL. Conclusions: As for the mechanism leading to cardiac arrest, it is thought that the histamines and leukotrienes released from cardiac mast cells caused a coronary artery spasm (Kounis syndrome). This anaphylactic shock is considered to be a result of anisakis allergy, but in general cases of anaphylaxis resulting from consumption of blue‐skinned fish.